Attention deficit hyperactivity disorder and student academic performance in Biology - Olubukola Joyce Olumide; Gabriel Segun Adewumi; Oluyemi Akinleye Ogundiwin (Inovasi Kurikulum, 2025)
The research investigates the influence of Attention Deficit Hyperactivity Disorder (ADHD) on the academic performance of Biology students in senior secondary schools in the Ondo East Local Government Area, Ondo State, Nigeria. The study adopted the descriptive survey research design. The study sample comprised 100 SSII Biology students in the Ondo East Local Government Area, Ondo State, Nigeria. The instrument used for data collection was the Attention Deficit Hyperactivity Disorder Questionnaire (ADHDQ). The instrument consisted of twenty items. Responses were based on a moderated Likert four-point rating scale. Experts in Biology, test measurement, and evaluation validated the instrument. A reliability coefficient of 0.85 was obtained. The Data collected were analyzed using mean and standard deviation to answer research questions. The findings showed that ADHD greatly influences students' academic performance in Biology. The issues of forgetfulness towards assignments, fidgeting, and blurting out answers all resulted in poor academic performance among ADHD students. It was recommended that the Government, parents, and Ministry of Education should pay close attention to affected students and find possible ways to help them. Trained counselors are to be employed and posted to all schools to provide counseling services to disordered (ADHD) students.    Abstrak Penelitian ini menyelidiki pengaruh Attention Deficit Hyperactivity Disorder (ADHD) terhadap prestasi akademik peserta didik Biologi di sekolah menengah atas di Ondo East Local Government Area, Negara Bagian Ondo, Nigeria. Penelitian ini mengadopsi desain penelitian survei deskriptif. Sampel penelitian terdiri dari 100 peserta didik Biologi SSII di Ondo East Local Government Area, Negara Bagian Ondo, Nigeria. Instrumen yang digunakan untuk pengumpulan data adalah Attention Deficit Hyperactivity Disorder Questionnaire (ADHDQ). Instrumen ini terdiri dari dua puluh item. Respons didasarkan pada skala penilaian empat poin likrt yang dimoderasi. Instrumen ini divalidasi oleh ahli biologi, pengukuran dan evaluasi tes. Koefisien reliabilitas diperoleh sebesar 0,85. Data yang dikumpulkan dianalisis menggunakan mean dan deviasi standar untuk menjawab pertanyaan penelitian. Temuan penelitian menunjukkan bahwa ADHD memiliki pengaruh besar terhadap prestasi akademik peserta didik di Biologi. Masalah pelupa terhadap tugas, gelisah, dan melontarkan jawaban semuanya mengakibatkan prestasi akademik peserta didik ADHD yang buruk. Direkomendasikan agar Pemerintah, orang tua, dan Kementerian Pendidikan memberikan perhatian yang seksama kepada peserta didik yang terdampak dan mencari cara yang mungkin untuk membantu mereka, konselor terlatih harus dipekerjakan dan ditempatkan di semua sekolah untuk memberikan layanan konseling kepada peserta didik yang mengalami gangguan (ADHD). Kata Kunci: Attention Deficit Hyperactivity Disorder (ADHD); Biologi; prestasi akademik